The Rising Price of Nonmarket Goods - Costa, Dora L; Kahn, Matthew E (American Economic Review, 2003)
Nonmarket goods such as unpaid household labor, leisure, health and longevity, and the environment are important components of the standard of living. They represent a large fraction of all activities. Prime-aged men and women spend 17 percent of their day in leisure activities, and 5 and 13 percent of their time, respectively, in unpaid housework compared to 23 and 13 percent of their time, respectively, in paid work. The quantity of nonmarket goods is rising over time. In the United States, life expectancy at birth is now 77 years, having risen by 29 years since 1900. In Los Angeles County between 1980 and 1998, average annual daily exceedences of the national smog standard declined by 60 days from 71 to 11. Falling big-city murder rates merit national news headlines. Studies of living standards have focused on the tremendous change in the quantity of nonmarket goods but have assumed that the value of nonmarket goods, except for unpaid labor, has remained constant. This assumption underlies most health studies (e.g., David Cutler and Elizabeth Richardson, 1997; Kevin M. Murphy and Robert H. Topel, 2003; William T. Nordhaus, 2003). Nordhaus (2003) valued declines in mortality since 1900 using a constant value of life. Even the Boskin CPI Commission (Michael J. Boskin et al., 1998) discussed trends in the quantity of nonmarket goods (i.e., pollution and crime progress) without mentioning incorporating such goods’ implicit prices into a broader CPI measure. There is no reason to think that implicit prices or the willingness to pay for nonmarket goods has remained constant. Rising real and shadow wages have made both leisure and unpaid household labor more expensive. Rising incomes have also made such normal goods as safety, health, a temperate climate, and the environment more valuable. We document the price dynamics of nonmarket goods by estimating repeat cross-sectional hedonic regressions. We focus on two important and measurable nonmarket goods: job fatality risk and climate. In both cases we find that both price and quantity have been rising. This evidence is consistent with rising valuation. We use our estimates of job-risk compensating differentials to construct new evidence on long-run trends in value of life. Accounting for price changes affects how we view the retrospective and prospective benefits of medical innovations. A rising value of life implies that marginal improvements in safety and in longevity are becoming more valuable. We report evidence that the price of living in a temperate winter and summer climate has significantly increased over time.